Kinetic characterization, antioxidant and in vitro toxicity potential evaluation of the extract M116 from Bacillus amyloliquefaciens, a Cuban southern coastmarine microorganism - Ilianet Céspedes; Fabiana Fuentes-León; Idania Rodeiro; Yoskiel Laurencio-Lorca; María V. Iglesias; José A. Herrera; Cindel Cuellar; Valia Caballero; Lis Pereira; Elizabeth Cuétara; Ángel Sanchez; Miguel D. Fernández; et al. (GarVal Editorial Ltda., 2023)
Abstract Context: Marine ecosystems are sources of bioactive compounds. Thirty-eight microorganism strains from the Cuban platform were screened, which allowed us to identify an extract from Bacillus amyloliquefaciens, strain CBM-116, as a source for obtaining bioproducts with biomedical applications. Aims: To physiologically characterize the culture of Bacillus amyloliquefaciens (CBM-116 strain) and to evaluate the antioxidant and toxic potentialities in vitro of the M116 extract obtained from CBM-116. Methods: The growth and metabolite production of the culture were evaluated at a sieve scale. The chemical composition of the M116 extract obtained from the fermented CBM-116 culture was qualitatively characterized. The extract antioxidant activity was measured by DPPH• and FRAP assays, while cytotoxicity was evaluated in MDCK, J774, CT26, 4T1, MCF-7, A549 cell lines and in Caulobacter crescentus, as well as the effects on genetic material by SOS colorimetric and Rifampicin Resistance, in the last model. Results: Grow kinetic parameters of CBM-116 showed the formation of protein metabolites, while the extract revealed antioxidant capacity, which was evidenced by its iron-reducing capacity. M116 was not cytotoxic up to 2000 μg/mL in C. crescentus; however, it induced mutagenicity and primary damage to the DNA of the bacteria. The extract significantly inhibited cell viability of CT26, 4T1, MCF-7, A549 cells after 48 hours' exposure. Mean inhibitory concentration (IC50) was calculated for CT26 and 4T1 cells with values of 384 and 488 µg/mL, respectively, in the MTT assay. In the neutral red assay, the values were 478.6 and 398 µg/mL, respectively. Meanwhile, the selectivity index showed values above 2 for both assays. MDCK and J774 cells were not affected. Conclusions: The M116 extract obtained from B. amyloliquefaciens showed bioactive properties with potential application for developing new anti-tumor agents.